Kierunki rozwoju lokalnego w opinii mieszkańców gminy Wiślica - Popławski, Łukasz (Direction of Local Development in the Opinion of Wislica District Inhabitants, 2005)
There are 72 municipalities in Świętokrzyskie Voivodship among which in 49 protected areas cover more than half of the area. These areas are usually landscape parks and protected landscape areas. One of those 49 is Wiślica municipality, which is covered by protected areas in 98%.The research is conducted among 111 inhabitants, who expressed their opinions in questionnaires. This dissertation presents the courses of development preferred by the inhabitants of municipality in the aspect of sustainable development. The research is based on inhabitants' opinions concerning particular courses of development, i.e. tourism, services, handicraft, industry and small business, agriculture, agricultural and food processing, and environmental protection.The results show that agriculture and agricultural products (76,4%), agriculture (77,2%) and tourism (70,0%) are the most preferred courses of development on the protected areas of Wiślica municipality, while the inhabitants chose the development of industrial potential, safety of inhabitants, shaping and protecting of environment to be the most important courses of actions for local authorities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 229-233